A calculation method of track shoe thrust on soft ground for splayed grouser. (June 2016) - Yang, Congbin; Cai, Ligang; Liu, Zhifeng; Tian, Yang; Zhang, Caixia
Highlights: A new method to predict thrust for track shoes on soft ground with splayed grouser. Soil moisture content, shear rate and grouser shape were taken into account. Model track shoe traction experiments were conducted for verification. Abstract: Thrust of track shoes on soft ground is affected by soil moisture content, shear rate and structure parameters of track shoes. A lack of comprehensive consideration of these factors exists for normal calculation methods. A method to predict thrust for track shoes on soft ground with splayed grouser was established based on experimental results and theoretical derivations. Model track shoe traction experiments were conducted for verification and correction of the thrust formula. It was observed that the thrust for the track shoes decreased with the increase in moisture content of the soil. Increases in shear rate, grouser height, and grouser splayed angle resulted in greater tractions. Effect of grouser thickness and grouser draft angle on tractions was not obvious. A corrected thrust formula allowed accurate prediction of thrust for a single track shoe on soft ground.